SATISFACTION AND ACCESSIBILITY CHALLENGES IN LIBRARY RESOURCE USAGE AMONG LEGAL PROFESSIONALS AND STUDENTS - Nandal, Parul; Singh, Jitender (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines satisfaction levels and accessibility challenges encountered by law students and legal professionals in using library resources. With a focus on both print and digital materials, it assesses key factors influencing satisfaction, including resource availability, technical support, and usability. Employing hypothesis testing and statistical analysis of data from 750 participants, findings reveal that satisfaction varies significantly across different academic and professional stages. While early-stage students express higher satisfaction with print resources, advanced students and professionals show a growing preference for digital resources, despite facing barriers like access restrictions and technical issues. Satisfaction with open access resources is generally positive, though issues with searchability and awareness limit their utility. The study emphasizes the need for law libraries to adopt a hybrid resource model that balances print and digital collections, enhances technical support, and promotes user education to address these accessibility challenges effectively.